Effect of the Irish Civil War 1922-1923 on suicide rates in Ireland: a retrospective investigation of the archives of the registrar-general for Saorstát Éireann (Epidemiology, Biostatistics, and Public Health, 2022)
Introduction: Emile Durkheim differentiated between two types of wars: National and Civil Wars in terms of effect on suicide mortality. This study investigates Durkheim’s assertion by examining the effect of Irish Civil War on the 1882-1928 suicide rates trend.Method: We used Auto-Regressive Integrated Moving Average with Explanatory variables (ARIMAX) design adopting Bayesian approach.Results: The odds for death by suicide for the total Irish population during the civil war period were calculated as 0.932 (95% CI: 0.753 to 1.125). This translates to a reduction in the suicide rates by 6.7% (95% CI: 24.7% to -12.5%). The odds for death by suicide for the total Irish population during the First World War period were calculated as 0.872 (95% CI: 0.754 to 0.997). This indicates to a reduction in the suicide rates by 12.8% (95% CI: 24.6% to 0.3%).Conclusion: Evidence from this study support a significant drop in terms of the intensity of suicidal behaviour in the Irish population during World War I more so than during the Irish Civil War.Conflict of interest: none
Keywords: suicide; Ireland; Irish Civil war; World War 1; Durkheim’s theory